ANALISIS PENILAIAN PRESTASI KERJA TERHADAP PROMOSI JABATAN KARYAWAN PT. BPRS SARANA PRIMA MANDIRI MEKASAN - Shalehoddin; R.A.Safira Isti Dwi Kurnia (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2020)
This study aims to determine whether the assessment of work performance has a positive and significant effect on employee promotion. This research was conducted from April to September 2020 at PT. BPRS Sarana Prima Mandiri Pamekasan Head Office. The population in this study were all employees totaling 20 people. The sampling used by this researcher was "saturated sample" where all members of the population were used as the sample of researchers, namely 20 employees. Independent Variables (X1) the quality of work results, (X2) the quantity of work , and (X3) timeliness of completion of work results. The dependent variable (Y) is promotion. Data analysis was performed using multiple linear regression analysis. The results showed that the quantity of work results and the timeliness of completion had a positive and significant effect on employee promotion, while the quality of work results had no effect.